Efficacy of Paracetamol in Closure of Ductus Arteriosus in Infants under 32 Weeks of Gestation - Tofe, Ines; Ruiz-González, Maria Dolores; Cañete, Maria Dolores; Pino, Asuncion; Rueda, Rosa Lorena; Parraga, Maria Jose; Perez-Navero, Juan Luis (Frontiers in Pediatrics, 2018)
Standard medical treatment for patent ductus arteriosus (PDA) closure has been indomethacin/ibuprofen or surgical ligation. Up to date, new strategies have been reported with paracetamol. The aim of this study was to present our experience with intravenous paracetamol for closing PDA in preterm neonates presenting contraindication to ibuprofen or ibuprofen had failed and no candidates for surgical ligation because of huge instability. Materials and methods. We conducted a retrospective case series study in a Neonatal Intensive Care Unit (NICU) from a tertiary hospital. 9 preterm infants ≤ 32 weeks of gestational age (GA) with hemodynamically significant PDA (hsPDA) were enrolled. They received 15 mg/kg/6h intravenous paracetamol for ductal closure. Demographic data and transaminase levels pre/post treatment were collected. Results. 30 preterm babies were diagnosed of hsPDA. 11/30 received ibuprofen with closure in 81,1% . 9 received intravenous paracetamol mainly due to bleeding disorders or thrombocytopenia. Successful closure on paracetamol was achieved in 7 out of 9 babies (77,7%). There was a significant increase in transaminase levels in 2 patients. They required no treatment for normalization. Conclusions. Paracetamol is an effective option in closure PDA. It should be a first line therapeutic option when there are contraindications for ibuprofen treatment. Transaminases must be checked during treatment. Key words. Patent ductus arteriosus, paracetamol, preterm, treatment.